Luigi Chiarelli : The Nature and Limits of the Pirandellian Playwright - Eagan, Maeve (Spunti e Ricerche, 2016)
Chiarelli was undoubtedly a great playwright but he was obscured by an even greater one: Luigi Pirandello. In this article, we will discuss Chiarelli’s Pirandellian humourist tendencies in his grotesque cycle of works and consider at which point these two playwrights merge and more importantly, at which point they diverge as their distinction still remains considerably blurred. In discussing these issues, we will determine the nature and limitations of Chiarelli’s work with the aim of answering the long-debated question regarding the merits of his contribution to Italian theatre.